Peningkatan Literasi Siswa Disleksia SDN 26 Ampenan dengan Mengadakan Kelas Literasi - Muhimmatul Khoiroh, Auliya; Binasti, Ayim; Listiani, Ni Putu Ayu; Mulia Asri, Nilam; Magfirah, Nurul; Syafitri, Rekha Hesti; Maulida Aulya, Zannur (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Dyslexia is a learning difficulty in children that causes difficulties in writing, reading, spelling and speaking, but there are also difficulties that generally appear between the ages of 7 and 12 years. Dyslexia factors are divided into three areas: educational, psychological, and biological. This service aims to describe dyslexia disorders in children, the factors that cause children to become dyslexic disorders, and educators' efforts to overcome the problem of dyslexia disorders and be able to understand the conditions experienced by people with dyslexia so that they can improve the literacy skills of dyslexic students. This service uses observation and interview methods and there are several stages of the implementation method. The service target consisted of 4 students from SDN 26 Ampenan. In this service, the writing team seeks to improve the literacy skills of dyslexic students. Students who experience dyslexia are affected by difficulty recognizing letters so they tend to experience delays during the learning process.